Analysis of chemical constituents and antinociceptive potential of essential oil of Teucrium Stocksianum bioss collected from the North West of Pakistan - Shah Syed Muhammad; Ullah Farhat; Shah Syed Muhammad; Zahoor Mohammad; Sadiq Abdul (BMC, 2012)
Abstract Background Medicinal plants are used for the treatment of different diseases in almost all cultures. Teucrium species grow wildly at different geographical locations around the world. Teucrium stocksianum is used in folk medicine for the treatment of diarrhea, cough, jaundice and abdominal pain. Scientific study on Teucrium stocksianum shows that it possesses anthelmintic, cytotoxic and antispasmodic activity. The aim of our present study is to identify the chemical composition and antinociceptive potential of the essential oil extracted from Teucrium stocksianum bioss. Method Essential oil (EO) from the aerial parts of Teucrium stocksianum were extracted by hydrodistillation process. The qualitative and quantitative composition of essential oil was determined with Gas chromatography/Mass spectrometer. Antinociceptive activity was determined by acetic acid induced writhing method. Percent inhibition of writhes of the test concentration was determined by comparing it with that of control. Tween-80 emulsion 2.5% (5 ml/kg b.w) was used as a control while Diclofenic sodium 50 mg/kg (b.w) was used as a standard drug. Results The chromatogram of the essential oil of Teucrium stocksianum shows differences both qualitatively and quantatively from essential oil composition reported in other countries. Hydrodistillation of Teucrium stocksianum yielded 0.4% (v/w), pale yellowish oil on dry basis. A total of 26 chemicals were identified by GC-MS accounting for 90.28% of the oil. The major components of essential oil were δ-cadinene (12.92%), α-pinene (10.3%), myrcene (8.64%), β-caryophyllene (8.23%), germacrene D (5.18%) and limonene (2.36%). Essential oil of Teucrium stocksianum has shown outstanding antinociceptive activity. It has been observed that increase in percent writhe inhibition (PWI) occurred from 20-80 mg/kg (b.w) and maximum writhe inhibition has been noted at a concentration of 80 mg/kg (b.w), but PWI decreased at 160 mg/kg, which may be due to some toxic effect of higher dose. ED50 value for Teucrium stocksianum was calculated as 31.5 ± 1.72415 mg/kg (b.w). Conclusion Our results indicate that there is a lot of variation in the composition of essential oil of Teucrium stocksianum boiss, which may be due to different climatic and experimental conditions. Secondly, the essential oil possesses strong antinociceptive activity and could be used in analgesic preparations especially for topical use.